YqfB protein from Escherichia coli: an atypical amidohydrolase active towards N(4)-acylcytosine derivatives - Stanislauskienė, Rūta (Sci Rep, 2020)
Human activating signal cointegrator homology (ASCH) domain-containing proteins are widespread and diverse but, at present, the vast majority of those proteins have no function assigned to them. This study demonstrates that the 103-amino acid Escherichia coli protein YqfB, previously identified as hypothetical, is a unique ASCH domain-containing amidohydrolase responsible for the catabolism of N(4)-acetylcytidine (ac4C). YqfB has several interesting and unique features: i) it is the smallest monomeric amidohydrolase described to date, ii) it is active towards structurally different N(4)-acylated cytosines/cytidines, and iii) it has a high specificity for these substrates (k(cat)/K(m) up to 2.8 × 10(6) M(−1) s(−1)). Moreover, our results suggest that YqfB contains a unique Thr-Lys-Glu catalytic triad, and Arg acting as an oxyanion hole. The mutant lacking the yqfB gene retains the ability to grow, albeit poorly, on N(4)-acetylcytosine as a source of uracil, suggesting that an alternative route for the utilization of this compound exists in E. coli. Overall, YqfB ability to hydrolyse various N(4)-acylated cytosines and cytidines not only sheds light on the long-standing mystery of how ac4C is catabolized in bacteria, but also expands our knowledge of the structural diversity within the active sites of amidohydrolases.